In vivo Assessment of Antioxidant and Wound Healing Improvement of a New Schiff Base Derived Co (II) Complex in Rats - El-Ferjani, R.M.; Ahmad, M.; Dhiyaaldeen, S.M.; Harun, F.W.; Ibrahim, M.Y.; Adam, H.; Mohd. Yamin, B.; Al-Obaidi, M.M.J.; Batran, R.A. (Nature Publishing Group, 2016)
Co (II) complex (CMLA) was investigated to evaluate the rate of wound healing in rats. Animals were placed into four groups: gum acacia, Intrasite gel, 10 and 20 mg/ml of CMLA. Wounds were made on the dorsal neck area, then treated with Intrasite gel or CMLA; both of these treatments led to faster healing than with gum acacia. Histology of the wounds dressed with CMLA or Intrasite gel displayed a smaller scar width, required less time to heal and showed more collagen staining and fewer inflammatory cells in comparison to wounds dressed with the vehicle. Immunohistochemistry for Hsp70 and TGF-β showed greater staining intensity in the treated groups compared to the vehicle group. Bax staining was less intense in treated groups compared to the vehicle group, suggesting that CMLA and Intrasite gel provoked apoptosis, responsible for the development of granulation tissue into a scar. CD31 protein analysis showed that the treated groups enhanced angiogenesis and increased vascularization compared to the control group. Furthermore, a significant increase in the levels of GPx and SOD and a decrease in MDA were also observed in the treated groups. This results suggest that CMLA is a potentially promising agent for the wounds treatment.